A Criticism of the British Left in Trevor Griffiths’s The Party in Light of ’68 Paris Student Riots - Özlem Özmen Akdoğan (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
Among the political playwrights of the post-war British drama, Trevor Griffiths is known for his commitment to socialist ideals and his continuous search for an ideal social(ist) structure in his works. Coming from a working-class background and having met many notable intellectual socialists prior to his dramatic career, Trevor Griffiths dedicated his playwriting to debate about the present and future of socialism in Britain and elsewhere. Despite Griffiths’s loyal attachment to socialism, his works provide a criticism of the left, left-wing parties, lack of unity among the proletariat, and lack of support and cooperation of the leftist parties in his country. The Party (1973) is one of those plays in which he provides a dialectical approach to an ideal understanding of socialism that is based on unity between the workers, the party as an organisation and the intelligentsia. Griffiths’s main concern is to lay out some of the reasons for the failure of the left and claim that a true socialist revolution can never be possible unless a commitment is achieved by all involved parties. This paper discusses socialist Trevor Griffiths’s play The Party as a criticism of the left in relation to prevalent concerns of Britain in the 1970s. While evaluating the reasons for Griffiths’s criticism, the discussion of the play is also related to the Paris student riots as a casein-point failed socialist revolution attempt due to similar problems Griffiths observes in his country.